CULTURAL DIVERSITY: : A LOOK AT LEGAL BASES, PEDAGOGICAL PRACTICES AND TEACHER EDUCATION - Maria do Monte, Jéssica; Santos Nascimento, Wisla; José dos Santos, Allison (Revista Gênero e Interdisciplinaridade, 2021)
Currently in Brazil, there is a great cultural wealth that is evident in social environments and practices. From a pedagogical point of view, it is extremely important to work with an approach aimed at cultural diversity, emphasizing the beauty of being multicultural. The objective of this work is to analyze, through the literature, the conception of cultural diversity from the perspective of legal bases as guidelines for teacher education and applicability of pedagogical practice. As a methodology, a basic and bibliographic research was chosen. For data collection, a literature review and analysis of primary bibliographic sources was used. From the complex point of view of the issues discussed, dealt with and, above all, the data analyzed in the universe of this study, it was possible to formulate a conclusive synthesis, presenting a set of conclusions that cultural diversity in the NCPs is seen as a cross-cutting theme, when applied through the pedagogical practice forms the fully educating so that their practices are positively reproduced in society. This time, it is up to the school to work pedagogically with students to develop a democratic and inclusive citizen attitude, as well as respecting differences, valuing identity and preserving cultural wealth. As well as the BNCC points out that cultural diversity is an approach that involves artistic and cultural manifestations, which in turn aims at valuing and preserving identity.